Dėl baltų *pat(is), *pat(n)ī pirminės reikšmės ir gramatinio statuso - Rosinas, Albertas (Baltistica, 2000)
ON THE ORIGINAL MEANING AND THE GRAMMATICAL STATUS OF BALTIC *pat(is), *pat(n)ī On the basis of the data from the Baltic and other Indo-European languages, the article rejects the common current view that Baltic *pat-root nouns, cf. Latv. pats ‘master, mister, husband’, pati ‘mistress, wife’, evolved from *pat-root pronouns with the meaning of ‘self’. The data from the Baltic languages lead to the conclusion that from Proto-Indo-European the Proto-Balts inherited the root noun of the consonantal declension *pat (<I.-E. *pot) ‘master, sovereign, mister, husband’ and the i̯ā-stem noun *patnī (<I.-E. *potnī) ‘mistress, sovereign, wife’. As far back as Proto-Baltic, as a result of word-final phonological changes, *pat (cf. I.-E. acc. sing. *potn̥> Baltic *patin and i-stem acc. sing. *avin) passed to the i-stem declension, i. e. it was modified to *patis and began to be declined as an i-stem noun, although also retaining some C-stem forms; under the influence of the *patis model, *patnī gradually lost the suffix *-n- and became *patī (>Lith. patì, Latv. pati). The assumption that the Baltic nouns *patis, *patnī did not evolve from pronouns could be supported by the following: (a) i-stem resp. C-stem pronominal paradigms are not characteristic of the Baltic pronominal systems; (b) moreover, the Prussian language (like the German, Slavonic and Indo-Iranian languages) never possessed *pat-root pronouns. In the East Baltic languages, pronouns with the meaning of ‘self’ evolved from the nouns *pat(is), *pat(n)ī in the process of pronominalization, which originally occurred in the sphere of the addressee and the non-participant person. In the process of pronominalization, *pat(is) eventually acquired endings typical of pronouns, cf. dat. sing, pačiam <— pačiamu(i), ines. sing, patime and a newer form pačiame, dat. pl. patiems ← patiemus. The identifying particle pat in the collocative pronouns toks pat, tokia pat cannot be related to the Hittite enclitic particle -pet (-pit). In the East Baltic languages, pat developed from the pronominalized inflectional forms *patis, *pati due to reduction. The Baltic languages showe a tendency to reduce the end of second components in fixed collocations with the meaning of category and classification, whereas second components in free collocations are not reduced, cf. the existing collocations aš pats ‘I myself’, tu pats ‘you yourself’, mes patys ‘we ourselves’, jūs patys ‘you yourselves’ and the non-existent ones °aš pat, °tu pat, °mes pat, °jūs pat, etc.